Theoretical Economics Faces a Serious Challenge - Jaroslav Daňhel; Eva Ducháčková; Jarmila Radová (European Financial and Accounting Journal, 2010)
The authors of the article point out that the theory of economics has failed to yield a solid theoretical background in such critical situations as the transformational period of post-communist economies and the period of the current financial and economic crisis. While classical liberal or Keynesian concepts are failing, theorists cannot look to mathematical modeling for help. The challenge for today's theoretical economists is to find a new concept for today's global era.
Keywords: D74; D81; D82; G22; 650; Determinism of stage of the Word; Decision making of economic subjects; Multifunction of mathematical models; Regulatory on financial market